2016
DOI: 10.1080/15427951.2016.1182952
|View full text |Cite
|
Sign up to set email alerts
|

Tree decompositions and social graphs

Abstract: Recent work has established that large informatics graphs such as social and information networks have non-trivial tree-like structure when viewed at moderate size scales. Here, we present results from the first detailed empirical evaluation of the use of tree decomposition (TD) heuristics for structure identification and extraction in social graphs. Although TDs have historically been used in structural graph theory and scientific computing, we show that-even with existing TD heuristics developed for those ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 103 publications
(270 reference statements)
0
24
0
Order By: Relevance
“…Clearly, graphs of connected tree-width < k also have tree-length < k, so by Theorem 1.1 the tree-length of G is bounded by the same function f (k, ) as its connected tree-width. In fact, Reidl and Sullivan [11,1] observed that the following better bound follows directly from of our lemmas for the proof of Theorem 1.1: Theorem 1.4. If G has tree-width < k and no geodesic cycle longer than , and G is not a forest, then the tree-length of G is at most (k − 2).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Clearly, graphs of connected tree-width < k also have tree-length < k, so by Theorem 1.1 the tree-length of G is bounded by the same function f (k, ) as its connected tree-width. In fact, Reidl and Sullivan [11,1] observed that the following better bound follows directly from of our lemmas for the proof of Theorem 1.1: Theorem 1.4. If G has tree-width < k and no geodesic cycle longer than , and G is not a forest, then the tree-length of G is at most (k − 2).…”
Section: Introductionmentioning
confidence: 67%
“…The tree-length of a graph G is the smallest value, minimized over all treedecompositions of G, of the maximum diameter in G of a part of this decomposition [6]. Reidl and Sullivan, see [11,1], noticed that our lemmas from Sections 3 and 4 can be applied directly to give a better bound on the tree-length of G than the bound of f ( , k) implied by Theorem 1.1: Theorem 1.4. If G has tree-width < k and no geodesic cycle longer than , and G is not a forest, then the tree-length of G is at most (k − 2).…”
Section: Tree-length and Hyperbolicitymentioning
confidence: 99%
“…It is worth emphasizing that the classical Barabási-Albert random tree model [5,34] belongs to this category. For a recent study of the treewidth parameter on real-world networks, see [1].…”
Section: Definition 3 (Treewidth)mentioning
confidence: 99%
“…It has been observed that hyperbolic embedding approaches could be used to map network's vertices on a multi-dimensional hyperbolic geometric space [15]- [18]. These spaces resemble well the structure of aggregationbased topologies.…”
Section: B Stationary Routing Protocolmentioning
confidence: 99%